2009
DOI: 10.1289/ehp.11513
|View full text |Cite
|
Sign up to set email alerts
|

Childhood Asthma and Environmental Exposures at Swimming Pools: State of the Science and Research Recommendations

Abstract: ObjectivesRecent studies have explored the potential for swimming pool disinfection by-products (DBPs), which are respiratory irritants, to cause asthma in young children. Here we describe the state of the science on methods for understanding children’s exposure to DBPs and biologics at swimming pools and associations with new-onset childhood asthma and recommend a research agenda to improve our understanding of this issue.Data sourcesA workshop was held in Leuven, Belgium, 21–23 August 2007, to evaluate the l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
91
0
4

Year Published

2009
2009
2021
2021

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 137 publications
(97 citation statements)
references
References 73 publications
2
91
0
4
Order By: Relevance
“…2 The harmful effects of chlorine appear to be dependent on concentration and length of exposure, and still require further study. 2,14 A 2009 study by Bemanian et al 15 showed significant improvement in peak expiratory flow rates in asthmatics after swimming, and suggested that indoor swimming is useful for patients with asthma, regardless of the potentially toxic effects of chlorine.…”
Section: Allergy Skin Testingmentioning
confidence: 99%
See 2 more Smart Citations
“…2 The harmful effects of chlorine appear to be dependent on concentration and length of exposure, and still require further study. 2,14 A 2009 study by Bemanian et al 15 showed significant improvement in peak expiratory flow rates in asthmatics after swimming, and suggested that indoor swimming is useful for patients with asthma, regardless of the potentially toxic effects of chlorine.…”
Section: Allergy Skin Testingmentioning
confidence: 99%
“…2 The benefits of swimming are also due to the horizontal position of the body, which provides a more adequate and constant breathing pattern compared with other forms of exercise, and to the high humidity present in pools. [2][3][4][5][6][7] The few studies published thus far (Table 1) on the effects of swimming in asthmatic individuals cannot be compared among one another due to methodological differences, which include type and duration of swimming program used, choice of outcomes, absence of a control group, and sample size determination issues.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Epithelial and mucosal damage caused by the exposure to chlorine products in children less than five years of age, pool attendants and competitive swimmers causes an early onset of asthma (Bernard et al, 2006). Children and youth are most susceptible to developing health effects because of the increasing use in youth for physical activity (Bougault et al, 2009) and they are likely to be swimming in water which is warmer and have higher levels of disinfectant (Weisel et al, 2009). …”
Section: Introductionmentioning
confidence: 99%
“…Some competitive swimmers develop VCD [59]. Children and adolescents who repeatedly swam, and were exposed to chlorine additives for water disinfection, could become symptomatic [75,[77][78][79][80][81][82]. Apparently, chlorine dissolved in swimming pool water would not pose a danger for the majority of swimmers.…”
Section: Discussionmentioning
confidence: 99%